PENGARUH LITERASI EKONOMI, JUMLAH UANG SAKU DAN MODERNITAS INDIVIDU TERHADAP PERILAKU MENABUNG MAHASISWA S1 PENDIDIKAN EKONOMI UNIVERSITAS NEGERI MALANG - lia tiana oktafiani; Agung Haryono (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2019)
This study aims to determine the effect of economic literacy, the pocket of money and individual modernity on the saving behavior of students of economic education at the State University of Malang. Data collection techniques using questionnaires and tests. This study uses the IBM SPSS 20 for windows program. The results of this study indicate that there is a significant influence on economic literacy, the pocket of money and individual modernity on saving behavior of students of economics education at Malang State University class of 2016.